External debt: an ethical view from the point of view of its effects - Flores Flores, Felix E. (2019)
The processes of indebtedness on the part of the states have been constant and carried out for various reasons in different countries.In the case of countries in the process of development or with problems to achieve it, different spaces have been created to modify the type of debt and the processes to pay it.However, all this generates a socio-economic problem that affects, especially, low-income citizens.In the present work, it is studied in depth the processes of indebtedness and, mainly, the modifications to them by means of the payment facilities. In turn, its impact is evaluated andcontrasted with an ethical view of the problem.